Assessment of the medicinal potentials of the methanol extracts of the leaves and stems of Buddleja saligna - Masika Patrick J; Koduru Srinivas; Jimoh Florence O; Adedapo Adeolu A; Afolayan Anthony J (BMC, 2009)
Abstract Background Buddleja saligna Willd (Loganiaceae) is a small to medium-sized evergreen tree; trunk short, often gnarled and crooked; crown dense, rounded or domed-shaped; foliage greyish green. The wild olives are traditionally used to lower blood pressures in many parts of the world. In southern Africa, bark and leaf decoctions are used to treat colic, coughs, colds, sore eyes, urinary problems and as purgatives. Methods The antibacterial, antioxidant activities and phenolic contents of the methanol extracts of the leaves and stems of Buddleja saligna were evaluated using in vitro standard methods. Spectrophotometry was the basis for the determinations of total phenol, total flavonoids, flavonols, and proanthocyanidins. Tannins, quercetin and catechin equivalents were used for these parameters. The antioxidant activities of the leaves and stem extracts of Buddleja saligna were determined by ABTS, DPPH, and ferrous reducing antioxidant property (FRAP) methods. Laboratory isolates of 10 bacteria species which included five Gram-positive and five Gram-negative strains were used to assay for antibacterial activity of this plant. Results The antioxidant activities of the leaves as determined by the ABTS and DPPH were similar to that of the stem. The flavonoids and the flavonols contents of the leaves were higher than that of the stem but the total phenols, proanthocyanidins and FRAP activities were higher in the methanol extracts of the stem. The extracts did show activity against both Gram-positive and Gram-negative bacteria. For instance, while the methanol extract of the leaves showed good activities on all the organisms except Serratia marcescens and Pseudomonas aeruginosa at MICs of between 2.5 and 5.0 mg/ml, the extract of the stem only showed activities on Bacillus cereus, Streptococcus pyrogens and Pseudomonas aeruginosa at the same concentration. Conclusion The results from this study indicate that the leaves and stem extracts of Buddleja saligna possess antioxidant properties and could serve as free radical inhibitors or scavenger or, acting possibly as primary antioxidants. Although, the antibacterial properties of Buddleja saligna are not as effective as the standard drugs-Chloramphenicol and Streptomycin, they still possess some activity against bacterial strains used in this study. Buddleja saligna may therefore be a good candidate for functional foods as well as pharmaceutical plant-based products.